Bringing It Home: A Study of the Incentives Surrounding the Repatriation of Foreign Earnings Under the American Jobs Creation Act of 2004 - BLOUIN, JENNIFER; KRULL, LINDA (Journal of Accounting Research, 2009)
ABSTRACT The American Jobs Creation Act of 2004 (the Act) creates a temporary tax holiday that effectively reduces the U.S. tax rate on repatriations from foreign subsidiaries from 35% to 5.25%. Firms receive the reduced tax rate by electing to take an 85% dividends received deduction on repatriations in 2004 or 2005. This paper investigates the characteristics of firms that repatriate under the Act and how they use the repatriated funds. We find that firms that repatriate under the Act have lower investment opportunities and higher free cash flows than nonrepatriating firms. Further, we find that repatriating firms increase share repurchases during 2005 by approximately $60 billion more than nonrepatriating firms, an amount that cannot be explained by differences in earnings between the two groups of firms. This increase represents about 20% of the $291.6 billion repatriated by our sample firms under the Act.